Causal relationship between plasma lipidome and rosacea: a Mendelian randomization analysis - Wang, Xiaoxue; Zhu, Zexin (Frontiers in Endocrinology, 2025)
BackgroundRosacea is a common chronic inflammatory skin disease. Limited studies reported the association between plasma lipidome and rosacea.MethodsWe employed a two-sample Mendelian randomization (MR) study to assess the causality between plasma lipidome and rosacea. Plasma lipidome association genome-wide association study (GWAS) data were collected. The inverse variance weighted (IVW) method was utilized as the principal method in our Mendelian randomization (MR) study; we also used the MR-Egger, weighted median, simple mode, and weighted mode methods. The MR-Egger intercept test, Cochran’s Q test, MR-Pleiotropy RESidual Sum and Outlier (MR-PRESSO), and leave-one-out analysis were conducted to identify heterogeneity and pleiotropy.ResultsA total of 179 lipid species were analyzed; among them, five lipid species were closely related to rosacea. Two species of sterol ester [sterol ester (27:1/22:6) and sterol ester (27:1/15:0)], two species of phosphatidylethanolamine [phosphatidylethanolamine (O-18:2_20:4) and phosphatidylethanolamine (18:0_20:4)], and one species of sphingomyelin [sphingomyelin (d34:0)] were causally associated with rosacea (P < 0.05). All of them play protective roles in patients with rosacea. No heterogeneity or pleiotropy was observed.ConclusionThis study provided new evidence of the relationship between plasma lipidome and rosacea. Our MR suggested that five lipid species play protective roles in rosacea progression. These could be novel and effective ways to treat rosacea.